In-vitro antifungal potential of myco versus bacteria synthesized ZnO NPs against chickpea and apricot pathogen - Junaid Ahmed; Farhana; Ghulam Ali Manzoor; Abdul Rasheed Kaleri; Bilal Zulfiqar; Abdul Waheed; Rashid Iqbal; Mehdi Rahimi (Scientific Reports)
Abstract Chickpea (Cicer arietinum) and Apricot (Prunus armeniaca) both are economically and nutritionally important, these both faces severe losses due to fungal Infections. For several fungal infections, traditional methods of management rely on chemical fungicideswhich have environmental and health risks. The in-vitro antifungal efficacy of myco-synthesized and bacteria-synthesized zinc oxide (ZnO) nanoparticles against pathogens impacting chickpea and apricot is aimed to be compared in this review article. Evaluated for their antifungal effectiveness against Fusarium oxysporum f. sp. ciceris in chickpea and Alternaria solani, myco-synthesized ZnO NPs generated from Trichoderma harzianum and bacteria-synthesized ZnO NPs were using a poisoned food approach, the study evaluated minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC), and inhibition zone diameter. At lower concentrations, myco-synthesized ZnO NPs shown better antifungal activity than their bacteria-synthesized counterparts, according to results. Surface changes, size, and concentration of nanoparticles were main determinants of antifungal activity. Emphasizing the need of more study to maximize the synthesis and application in agricultural environments, this review underlines the possibilities of ZnO NPs as sustainable substitutes for chemical fungicides.